The Relationship Between Insulin Resistance and Cortisole Levels - Ceren Gür; Mustafa Boz; Cüneyt Müderrisoğlu; Hayri Polat (İstanbul Medical Journal, 2015)

(untitled)
Objective: It is known that cortisol, which is controlled by hypothalamic–pituitary– adrenal axis and produced by the adrenal gland results in glucose intolerance, obesity, and hypertension (such as in Cushing’s syndrome). Insulin resistance is understood as the down regulation of insulin-mediated glucose release from the liver or impaired insulin-mediated peripheral glucose utilization. Glucocorticoids (cortisol), as counter-insulin hormones, suppress insulin secretion from pancreatic beta cells. On the other hand, they increase vagal stimuli to release insulin as the central effect. The balance between these effects may cause compensatory hyperinsulinemia and hyperglycemia. In this study, we investigate the relationship between cortisol levels, insulin, and glucose metabolism of 154 patients with obesity who were admitted to the endocrinology outpatient clinic. Methods: One hundred and fifty-four patients who were admitted to the endocrinology outpatient clinic (42 males and 112 females) were investigated with cross-sectional and retrospective statistical methods. Results: The main features of patients (average±standard deviation) were as follows: age: 49.8±14.8 years; weight: 84.5±18.7 kg; BMI: 32.24±7.51 kg/ m2; waist circumference: 98.97±16.34 cm; waist-to-hip ratio: 0.87±0.07; systolic blood pressure: 128±19.26 mmHg; diastolic blood pressure: 78.3±9.6 mmHg; fasting blood glucose: 110.3±48.62 mg/dL; HbAlc: 5.74%±1.35%; insulin: 12.21±1.41 μU/mL; C-peptide: 3.04±l.71 ng/mL; cortisol: 14.30±7.75 μg/dL; LDL-cholesterol: 145.20±64.03 mg/dL; HDL-cholesterol: 43.31±12.25 mg/dL. It was observed that cortisol levels increased with age, therefore, increasing fasting plasma glucose, HbAlc, and C-peptide levels, and low HDL levels. In addition, the upper limit levels of cortisol were found to be together with minimal elevated levels of prolactin and, particularly WHR (waist-to-hip ratio), which is an indicator of abdominal obesity. Conclusion:Increased cortisol release can disrupt glucose tolerance and insulin secretion, particularly for individuals with abdominal obesity.